Study of melanin distribution in the hair cells of Karakul lambs of different colours - Lakhanova, K. M.; Kedelbaev, B.; Yeleugaliyeva, N.; Korazbekova, K. (Small Ruminant Research, 2022)
The relevance of this study is explained by the need to have a more accurate instrument for assessing the phenotype of Karakul lambs by colour. Despite the fact that the colouring of Karakul lambs is an important sign for obtaining a high-quality krimmer skin, its determination occurs only visually, which leads to large errors. This fact indicates the need for a more objective method for assessing the colour of Karakul lambs. In this regard, this article is aimed at studying melanin distribution type in cortical layer cells of Karakul lambs’ hair of different colours and evaluating the possibility of using this trait as an additional criterion for identifying the phenotype by lear. After the preparation of smears from hair macerates, light microscopy was performed with a visual count of cells with a particular distribution pattern of melanosomes in cells, according to the chosen classification. The absence of class zero cells (complete absence of melanin) for black lambs was revealed, however, there were unexpectedly quite few cells of the fifth class (with superpigmentation). The largest number of cells of grey lambs were assigned to the third or zero classes. With an increase in the cells of the zero class, the colour intensity of the taken hair also decreases. In lambs of medium-blue and dark-blue colours, cells of the third class prevailed. The materials of the article are of practical value for breeding work with Karakul sheep, providing more accurate control of the selection of sheep to achieve the desired result using a quantitative parameter. Актуальность данного исследования обусловлена необходимостью иметь более точный инструмент для оценки фенотипа каракульских ягнят по окраске. Несмотря на то, что окраска каракульских ягнят является важным признаком для получения качественной криммерной шкуры, ее определение происходит только визуально, что приводит к большим погрешностям. Этот факт указывает на необходимость более объективного метода оценки окраса каракульских ягнят. В связи с этим данная статья направлена на изучение типа распределения меланина в клетках коркового слоя шерсти каракульских ягнят разной окраски и оценку возможности использования этого признака в качестве дополнительного критерия для выявления фенотипа по лиру. После приготовления мазков из мацератов волос проводили световую микроскопию с визуальным подсчетом клеток с определенным характером распределения меланосом в клетках согласно выбранной классификации. Выявлено отсутствие клеток нулевого класса (полное отсутствие меланина) у черных ягнят, однако неожиданно довольно мало клеток пятого класса (с суперпигментацией). Наибольшее количество клеток серых ягнят было отнесено к третьему или нулевому классам. С увеличением клеток нулевого класса снижается и интенсивность окраски взятых волос. У ягнят средне-голубого и темно-синего окрасов преобладали клетки третьего класса. Материалы статьи имеют практическое значение для племенной работы с каракульскими овцами, обеспечивая более точный контроль подбора овец для достижения желаемого результата по количественному показателю.
Keywords: импакт-фактор 2022; зарубежное издание; периодическое издание; научный журнал; зарубежные авторы; овцеводство; каракулеводство; каракульские ягнята; окраска ягнят; скопус